KESESUAIAN MATERI DEUTSCH ECHT EINFACH TEMA FREIZEITAKTIVITÄTEN DENGAN KURIKULUM MERDEKA DALAM KETERAMPILAN BERBICARA BAHASA JERMAN KELAS XI - Santary Jehabat, Florentine Morella; Pujosusanto, Ari (LATERNE, 2025)
“Deutsch Echt Einfach” is one of the textbooks used for teaching the German language at the secondary school level. Each chapter in this book is organized around themes relevant to students’ everyday lives, such as family, leisure activities, and destinations etc. These themes support the development of speaking skills and enhance students’ understanding of German culture. This study aims to examine the alignment of the Deutsch Echt Einfach textbook, specifically the theme Freizeitaktivitäten, with the Merdeka Curriculum, focusing on German speaking skills for Grade XI students. A qualitative research method was employed using a literature review (documentation) technique. The analysis process consists of data reduction from the textbook, material suitability analysis using a comparison table of tasks (Aufgaben) with the CP, TP, and ATP, assessment of relevance level, and conclusion. The results indicate that the content of the Deutsch Echt Einfach textbook aligns with the Learning Outcomes, Learning Objectives, and Learning Objective Pathways of the Merdeka Curriculum phase F, particularly in the Speaking element. Therefore, the textbook can be considered a relevant and supportive teaching resource for implementing the Merdeka Curriculum in schools. Keywords: Material Suitability, “Deutsch Echt Einfach” books, German language learning.